Protonated Phosphazenes: Structures and Hydrogen‐Bonding Organocatalysts for Carbonyl Bond Activation. Issue 7 (4th February 2016) - Jardel, Damien; Davies, Clotilde; Peruch, Frédéric; Massip, Stéphane; Bibal, Brigitte
Abstract: The synthesis and application of protonated phosphazeniums as hydrogen‐bond donor groups was demonstrated in the solid state and in solution. In particular, their catalytic activity was shown in the activation of the carbonyl group within cyclic esters, using a benchmark reaction, that is, in the ring‐opening polymerization of lactide and valerolactone, in the presence of a basic co‐catalyst. The reactions proceed differently depending on monomers and/or phosphazenium salts. The impact of catalysts and reactants steric hindrance upon the outcome of the reaction is then highlighted and discussed. Abstract :